Agrobacterium expressing a type III secretion system delivers Pseudomonas effectors into plant cells to enhance transformation - Raman, Vidhyavathi; Rojas, Clemencia M.; Vasudevan, Balaji; Dunning, Kevin; Kolape, Jaydeep; Oh, Sunhee; Yun, Jianfei; Yang, Lishan; Li, Guangming; Pant, Bikram D.; Jiang, Qingzhen; Mysore, Kirankumar S. (Nature communications, 2022)
Agrobacterium -mediated plant transformation (AMT) is the basis of modern-day plant biotechnology. One major drawback of this technology is the recalcitrance of many plant species/varieties to Agrobacterium infection, most likely caused by elicitation of plant defense responses. Here, we develop a strategy to increase AMT by engineering Agrobacterium tumefaciens to express a type III secretion system (T3SS) from Pseudomonas syringae and individually deliver the P. syringae effectors AvrPto, AvrPtoB, or HopAO1 to suppress host defense responses. Using the engineered Agrobacterium , we demonstrate increase in AMT of wheat, alfalfa and switchgrass by ~250%–400%. We also show that engineered A. tumefaciens expressing a T3SS can deliver a plant protein, histone H2A-1, to enhance AMT. This strategy is of great significance to both basic research and agricultural biotechnology for transient and stable transformation of recalcitrant plant species/varieties and to deliver proteins into plant cells in a non-transgenic manner. Agrobacterium infection can cause defense responses in many plants, which leads to transformation recalcitrance. Here, the authors express type III secretion system in Agrobacterium to deliver effector proteins into plant cells to suppress host defense responses and thus enhance transformation in some plant species.